Avaliação visual da saúde de solos sob diferentes usos - Bevilaqua, Lucas José (2017)
Defining when an agroecosystem can be considered healthy is one of the challenges faced by both family farmers and extension workers and researchers. There are several methodologies of visual evaluation of indicators that indicate their health and the first chapter is a bibliographical review on the methods of visual evaluation of the soil. The second chapter deals with a fieldwork in which seven methods for the determination of soil visual assessment indexes (IAVS) in six different soil uses, including the Visual Soil Health Assessment Method (AVSS), modified in this research and with emphasis on edaphic macrofauna. The study was carried out at the São Sebastião site, located in the city of Terra Roxa (SP) in areas of riparian forest (MCI), agroforestry system (SAF), organic sugar cane (CAN) and orchard (POM), all in Red Latosol, in a permanent preservation area (APP) and pasture (PAS), both in Gleissolo. MCI and SAF and APP treatments, which had greater plant diversity and tree species, had the highest IAVS. The AVSS proved to be useful and highly sensitive in the evaluation of soil quality in the different management systems analyzed in the property. The third chapter discusses the use of soil macrofauna as a soil health bioindicator and how it can be included in soil visual assessment methods in a simple and accessible way for farmers. Ten groups of edaphic macrofauna were found, as well as eggs and larval stages, including animals that perform several ecological functions in the soil. The diversity of macrofauna was higher in the areas that received the highest indices in the visual evaluations of the soil. The SAF presented the highest diversity of invertebrate macrofauna in the soil. Soil management and tillage systems affect the structure of the dominant taxonomic groups of the edaphic macrofauna. Soil fauna can be used as a bioindicator of soil health.